Метеорит Оханск: особенности состава, строения и генезиса - Бахтин Анатолий Иосифович; Сонин Геннадий Владимирович; Сунгатуллин Рафаэль Харисович; Петрова Римма Даниловна (Федеральное государственное автономное образовательное учреждение высшего образования «Казанский (Приволжский) федеральный университет», 2016)
Методами кристаллооптики, рентгенофлуоресцентным, рентгенофазовым и электронного микрозонда исследовано вещество метеорита Оханск. Показано, что метеорит является обыкновенным оливин-бронзитовым хондритом. Его главные силикатные минералы представлены оливином, бронзитом, плагиоклазом, диопсидом, а главные рудные минералы камаситом, троилитом. Метеорит содержит довольно много силикатного стекла. Анализ особенностей состава и строения метеорита Оханск позволил сделать вывод о том, что он образовался на ранней стадии аккреции расплавленного вещества Протосолнечной туманности и не претерпел эндогенных термобарических преобразований. По-видимому, его вещество не погружалось глубоко в недра материнского тела, поэтому оно сохраняет информацию о ранних стадиях аккреции протопланетного газопылевого вещества.The Okhansk meteorite fell on August 18, 1887 near the village of Tabor, about 15 km away from the town of Okhansk in Perm province and weighed 186.5 kg (the total weight of collected fragments, according to P.I. Krotov, was more than 245 kg). The shock wave from the meteorite entry knocked down animals and riders on horses. Despite the fact that it was significantly stronger than that caused by the Chelyabinsk meteorite of 2013, all information about this meteorite has completely erased from people’s memory. It has been shown that the meteorite is an ordinary olivine-bronzite chondrite. Its main silicate minerals are olivine, bronzite, plagioclase, and diopside. The main ore minerals are kamacite and troilite. The meteorite contains silicate glass in large amounts. The analysis of the composition and structure of the Okhansk meteorite has demonstrated that it was formed at the early stages of accretion of the melted substance of the protosolar nebula without undergoing endogenous, temperature, or pressure changes.
Keywords: МЕТЕОРИТ ОХАНСК; ХОНДРИТЫ; ПРОТОСОЛНЕЧНАЯ ТУМАННОСТЬ; ГЕНЕЗИС; OKHANSK METEORITE; CHONDRITES; PROTOSOLAR NEBULA; GENESIS; 523.681